Синтез та фізико-хімічні властивості S-заміщених похідних 3-бензил-8-метил-7-[(4-феніл-5-тіо-4H-1,2,4-тріазол-3-іл)метил]ксантину - Левіч, Сергій Вадимович; Шкода, Олександр Станіславович; Александрова, Катерина Вячеславівна; Левич, С. В.; Шкода, А. С.; Александрова, Е. В.; Levich, S. V.; Shkoda, А. S.; Alexandrova, K. V. (Запорізький державний медичний університет, 2013)
Розроблено препаративну методику отримання S-заміщених похідних 3-бензил-8-метил-7-[(4-феніл-5-тіо-4H-1,2,4-тріазол-3-іл)метил]ксантину, структуру яких підтверджено даними елементного аналізу, ПМР-спектроскопії та мас-спектрометрії. Разработана препаративная методика получения S-замещенных производных 3-бензил-8-метил-7-[(4-фенил-5-тио-4H-1,2,4-триазол-3-ил)метил]ксантина, структура которых подтверждена данными элементного анализа, ПМР-спектроскопии и масс-спектрометрии. The preparative methodic of obtaining of S-substituted derivatives of 3-benzyl-8-methyl-7-[(4-phenyl-5-thio-4H-1,2,4-triazol-3-yl)methyl]xanthines was developed. The structure of synthesised compounds was proved by elemental analysis, NMR-spectroscopy and mass-spectrometry data.
Синтез и физико-химические свойства S-замещенных производных 3-бензил-8-метил-7-[(4-фенил-5-тио-4H-1,2,4-триазол-3-ил)метил]ксантина
Synthesis and physico-chemical properties of S-substituted derivatives of 3-benzyl-8-methyl-7-[(4-phenyl-5-thio-4H-1,2,4-triazol-3-yl)methyl]xanthines
Keywords: ксантини; синтез; ПМР-спектроскопія; мас-спектрометрія; ксантины; ПМР-спектроскопия; масс-спектрометрия; xanthines; synthesis; NMR-spectroscopy; mass-spectrometry